Sensor networks with IEEE 802.15.4 systems distributed processing, MAC, and connectivity - Buratti, Chiara; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book presents a simple, yet complete, approach to the design and performance analysis of distributed processing algorithms and techniques suitable for IEEE 802.15.4 networks. In particular, the book focuses on the bottom two layers of the ISO/OSI stack (Physical and Medium Access Control), discussing also a few issue related to routing. The book is a the synergistic combination of signal processing aspects on the one hand and MAC and connectivity issues on the other hand. The goal of the book is to clearly link physical layer aspects with medium access and topology aspects, in order to provide the reader with a clear understanding of how to approach the design of proper distributed signal processing and medium access algorithms in this context.
PART I: Wireless Sensor Networks -- Distributed Detection of Spatially Constant Phenomena -- Distributed Detection of Spatially Non-Constant Phenomena -- PART II: Tree-Based Topologies for Multi-Sink Networks -- Performance Analysis of the IEEE 802.15.4 MAC Protocol -- Area Throughput for Multi-Sink Wireless Sensor Networks -- PART III: Cross-layer Design and Performance Analysis.
Electronic reproduction.
Keywords: Wireless sensor networks; Wireless Metropolitan Area networks -- Standards